CuO/TiO2 nanocomposite photo-anode for dye-sensitized solar cells - Elbushra, H. A.; Liew, J. Y.C.; Talib, Z. A.; Ahmed, M.; Wardi, H.; Eassa, N. (Springer Nature, 2025)
Abstract: Titanium dioxide (TiO2) nanoparticles were synthesized via a hydrothermal method using titanium bis(ammonium lactato) dihydroxide as a precursor and confirmed by X-ray diffraction (XRD) analysis to exhibit the crystalline anatase phase. Ultraviolet–visible (UV–Vis) spectroscopy revealed that TiO2 primarily absorbs in the ultraviolet region. High-resolution transmission electron microscopy (HRTEM) characterized the particle morphology and size distribution. A CuO/TiO2 nanocomposite was then prepared, with XRD confirming the coexistence of monoclinic CuO and anatase TiO2 phases. UV–Vis spectra demonstrated enhanced light absorption in the visible region due to CuO incorporation. Photo-anodes based on these materials were tested in dye-sensitized solar cells (DSSCs) fabricated via the doctor-blade technique. I–V measurements showed that DSSCs with CuO/TiO2 photo-anodes achieved a 2.1% efficiency, surpassing pure TiO2-based DSSCs (1.7%). This improvement is attributed to better light absorption and electron transfer. These findings highlight the potential of CuO/TiO2 nanocomposites to enhance DSSC performance, contributing to the advancement of cost-effective solar energy technologies.